Analisis Proses Diagnosis Kerusakan Clutch Kompresor AC Mobil Nissan X-Trail T30 Menggunakan Scanner Universal - Johan Christofer Zega; I Wayan Dikse Pancane (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study analyzed an open-circuit fault in the air-conditioning compressor-clutch circuit of a Nissan X-Trail T30 using a universal OBD-II scanner and a digital multimeter. The vehicle exhibited a non-cooling condition: the blower and A/C indicator operated, but the compressor clutch did not engage. The diagnosis was conducted sequentially from the control request to the actuator response. Scanner data confirmed communication with the engine control module and an accepted A/C request. Electrical measurements confirmed that the 10 A A/C fuse, relay supply, relay contact, and voltage at A/C relay E5 terminal 5 were normal. However, battery voltage was absent at compressor connector E34 terminal 1, and continuity testing between E5 terminal 5 and E34 terminal 1 indicated an open circuit (OL). Direct battery activation produced an engagement click, confirming that the magnetic clutch remained functional. After repair of the cable or connector, continuity and supply voltage at E34 were restored and the clutch operated normally. All measurements relevant to the electrical-diagnosis objective were completed and reported categorically according to Nissan service-manual criteria, covering voltage availability, continuity status, and clutch response. The findings show that scanner information must be combined with voltage, continuity, and direct-actuation tests to localize electrical faults and prevent unnecessary compressor replacement.